Ambush Marketing: A Chinese Perspective - Liu, Yuqi (Université d'Ottawa / University of Ottawa, 2013)
As one of the top topics in both scholarly and practical fields of sport sponsorship, ambush marketing research usually focuses on protection of the sports sponsor’s rights. Since five years after the 2008 Games, how China performs sponsor protection record after the Olympics should be evaluated. In response to the question, the investigator conducted a qualitative study involving 11 semi-structured interviews of subject-matter experts from various types of organizations in China and an archive content analysis. The interviews aimed at revealing further insights into how ambush campaigns are perceived within China as well as to further its possible sociological and economical causes. Results revealed that although ambush marketing was regulated during the 2008 Olympics, it is still common in China. The current situation of ambush marketing in China is shaped by five factors including: (1) media, (2) legal system, (3) government relationships, (4) event organizers’ experience, and (5) contemporary culture.
Keywords: sports sponsorship; China; ambush marketing; experts